Potato Consumption Is Not Associated with Cardiometabolic Risk in Adolescent Girls. (29th May 2020) - Yiannakou, Ioanna; Yuan, Mengjie; Pickering, R Taylor; Singer, Martha; Moore, Lynn l
Abstract: Objectives: Potatoes are typically considered to be less healthy than most vegetables although the 2015 Dietary Guidelines provide no specific recommendations for intake other than to reduce consumption of fried potatoes. Evidence linking potato consumption, including consumption of fried potatoes with a risk of obesity, is limited. The objective of the current analysis was to study the impact of potato consumption on the risk of obesity and elevated cardiometabolic risk (CMR) in adolescent girls. Methods: We used data for 2091 girls, ages 9–10 years at enrollment in the prospective National Growth and Health Study (NGHS). and followed for 10 years. Potato consumption was derived from 3-day records collected during the annual follow-up periods. Total potato intake included white and sweet potatoes from all sources including mixed dishes. Total intake was classified as <0.25 (low), 0.25–<0.5 (moderate), and 0.5–<1.0 (high) cup-equivalents per day. Logistic regression models were used to estimate the odds ratio for becoming overweight or developing elevated blood pressure, triglyceride levels, or fasting glucose at 17–20 years of age according to the category of potato consumption. Models adjusted for confounding by factors such as age, race, socio-economic status, BMI, the hour spent watching TV per day, and other dietary factors. Results: At 9–17 years of age, the median intake of total potatoes was 0.38 cups/day. Girls with moderate intakes of potatoes had a 23% lower risk (95% CI: 0.57–1.04) of being overweight (>85% ile of CDC cutoff values); the effects of higher intakes were the same. The odds ratio for elevated blood pressure (≥90th percentile for age, sex, height) associated with moderate (vs. low) intakes of potatoes was 1.16 (95% CI: 0.84–1.59) and again, the effects of higher intakes were very similar. For the relation between potatoes and elevated triglycerides (≥110 mg/dl), the risk was U-shaped with those who had moderate (vs. low) intakes having a 24% lower risk (95% CI: 0.54–1.08). Finally, moderate and higher (vs. lower) potato intakes were linked with non-statistically significant 26% and 30% reduced risks of elevated fasting glucose levels, respectively. Conclusions: These analyses suggest that there is no adverse effect of moderate daily potato consumption on cardiometabolic risk in adolescent girls. Funding Sources: The Framingham Heart Study.